CRPD and transformative equality. Issue 1 (15th February 2017) - Minkowitz, Tina
Abstract: This reflection responds primarily to the papers on legal agency and state intervention, with brief comments on the two other papers. The concept of transformative equality, developed in jurisprudence under the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), can promote a deeper understanding of the rights of persons with disabilities. 1 In particular, it is useful to address power relations between disabled and non-disabled persons not only with respect to family members and medical professionals, but also in the institutions of law and the state.